2014
DOI: 10.1002/mds.25987
|View full text |Cite
|
Sign up to set email alerts
|

Pallidal gap junctions‐triggers of synchrony in Parkinson's disease?

Abstract: Although increased synchrony of the neural activity in the basal ganglia may underlie the motor deficiencies exhibited in Parkinson's disease (PD), how this synchrony arises, propagates through the basal ganglia, and changes under dopamine replacement remains unknown. Gap junctions could play a major role in modifying this synchrony, because they show functional plasticity under the influence of dopamine and after neural injury. In this study, confocal imaging was used to detect connexin-36, the major neural g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 63 publications
1
33
0
Order By: Relevance
“…Yet, increased abundance of GJs could also contribute to β oscillations since 43% more Cx36 was reported in the GPe of PD patients than matched controls (Schwab et al, 2014). The GPi also had marked increases in Cx36, but none were observed in the STN (Schwab et al, 2014). In the future, we could directly inject TMA into the right GPe of hemiparkinsonian rats to see if further increase in dominant β oscillatory activity was observed.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Yet, increased abundance of GJs could also contribute to β oscillations since 43% more Cx36 was reported in the GPe of PD patients than matched controls (Schwab et al, 2014). The GPi also had marked increases in Cx36, but none were observed in the STN (Schwab et al, 2014). In the future, we could directly inject TMA into the right GPe of hemiparkinsonian rats to see if further increase in dominant β oscillatory activity was observed.…”
Section: Discussionmentioning
confidence: 92%
“…Since a lack of dopamine has been shown to increase GJ activity in cells in other BG nuclei (Cepeda et al, 1989;Grace, 1994, 1999) and PD patients can lose 82% of dopamine in the GPe (Rajput et al, 2008), we speculate that this could underlie the emergence of β oscillatory activity in PD. Yet, increased abundance of GJs could also contribute to β oscillations since 43% more Cx36 was reported in the GPe of PD patients than matched controls (Schwab et al, 2014). The GPi also had marked increases in Cx36, but none were observed in the STN (Schwab et al, 2014).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Although increased synchrony of the neural activity in the basal ganglia may underlie the motor deficiencies exhibited in sPD, gap junctions could play a major role in modifying this synchrony because they show functional plasticity under the influence of dopamine and after neural injury. Gap junctions act as a powerful modulator of synchrony in the basal ganglia [56]. Each neurobiological molecule of gap junction pathway gained from our study is shown in Table 2, which showed that the partial loci and/or genes in the embryonic development, the electrical coupling, the metabolic transport, apoptosis, the maintaining cellular homeostasis, and growth control participated in the pathogenesis of sPD, which could be associated with the generation of alpha-synuclein.…”
Section: Discussionmentioning
confidence: 97%